Peristiwa Tutur Kata Mangga dan Matur Nuwun dalam Masyarakat Jawa: Kajian Sosiolinguistik: Speech Event of Mangga and Matur Nuwun Words in Javanese Community: Sociolinguistic Study - Dwi Atmawati (Balai Bahasa Provinsi Papua, 2020)
This Javanese language use research focuses on review on meaning of words dealing with extralingistic factor. Therefore, the writer is interested to research the speech expression using Javanese language in relation to extralinguistic factor. This research focuses on the review of the word mangga ‘sila’ in Indonesian and matur nuwun ‘terima kasih’ in Indonesian. Those two words are reviewed from sociolinguistic aspect. The aim of the research is to explain the meaning of the word mangga and matur nuwun through the understanding of speech expression. To discuss the problem formulation the writer uses semantic and sociolinguistic theories. This research also uses descriptive qualitative approach. The objects are the data of speech which contain the words of “matur nuwun” and “mangga” in Javanese society on the common and family level located in the districts of Borobudur, Magelang. The data source comes from oral speech. The data is obtained through the method of listening, recording, noting the conversation. The result shows that the word mangga is a kind of Javanese krama language addresses to partner of speaking to appreciate them. The word mangga is meaningful to ask sincerely and ask just as courtesy. The word “matur nuwun” can be meaningful as grateful sincerelu and as soft refusal. The proper meaning can only be understood through the understanding of the expression when it is uttered.